Vehicle restrictions and CO2 emissions in Beijing – A simple projection using available data. (December 2015) - Li, Peiheng; Jones, Steven
Highlights: Analyze the vehicle ownership restraint policy in Beijing and its effect on private vehicle population. Analyze its potential effectiveness in mitigating CO2 emissions. The CO2 emissions reduction benefit will become more apparent in the near future. The policy will be very effective in controlling the growth of private passenger vehicles and thus CO2 emissions. Abstract: The Beijing Government launched a new policy on restricting vehicle ownership in late 2010 to regulate the faster motorization and the excessive vehicular carbon dioxide (CO2 ) emissions. In this paper, we first analyzed this policy and its effect on private passenger vehicle population. The private passenger vehicle population in Beijing from 2011 to 2020 was predicted under three different scenarios: no constraint (NC), current constraint (CC) and tighter constraint (TC). Then the assessment of vehicular emissions reduction benefits was made on the basis of private passenger vehicle population, vehicle kilometers traveled and CO2 emission factors. It was projected that the CO2 emissions in 2020 will reach 23.90, 15.55 and 13.23 million tons under NC, CC and TC respectively. The policy is very effective in controlling the faster motorization and reducing CO2 emissions.